Sexual arousal and masculinity-femininity of women. [article]. - Rieger, Gerulf
Studies with volunteers in sexual arousal experiments suggest that women are, on average, physiologically sexually aroused to both male and female sexual stimuli. Lesbians are the exception because they tend to be more aroused to their preferred sex than the other sex, a pattern typically seen in men. A separate research line suggests that lesbians are, on average, more masculine than straight women in their nonsexual behaviors and characteristics. Hence, a common influence could affect the expression of male-typical sexual and nonsexual traits in some women. By integrating these research programs, we tested the hypothesis that male-typical sexual arousal of lesbians relates to their nonsexual masculinity. Moreover, the most masculine-behaving lesbians, in particular, could show the most male-typical sexual responses. Across combined data, Study 1 examined these patterns in women's genital arousal and self-reports of masculine and feminine behaviors. Study 2 examined these patterns with another measure of sexual arousal, pupil dilation to sexual stimuli, and with observer-rated masculinity-femininity in addition to self-reported masculinity-femininity. Although both studies confirmed that lesbians were more male-typical in their sexual arousal and nonsexual characteristics, on average, there were no indications that these 2 patterns were in any way connected. Thus, women's sexual responses and nonsexual traits might be masculinized by independent factors. -- (from the authors)